Efek Moderasi Religiousity pada Money Ethics dan Teknologi Informasi Terhadap Tax Evasion Pada UMKM di Kecamatan Serpong - Rosita Wulandari (Accounthink, 2020)
Abstract The purpose of this research is to obtain empirical evidence of the influence of money ethics and information technology taxation on tax evasion with religiosity as a moderation variable in MSME actors of Serpong sub-district registered in the cooperative and msme office of South Tangerang city. The population in this study is all Serpong sub-district smes registered with the South Tangerang City Cooperative and MSME Office. The sample of this study was determined by purposive sampling method and the data was collected by the division of questionnaires with the number of respondents 105 respondents, questionnaires that can be processed as many as 100 respondents, the rest of the data filled in incomplete. The data analysis methods used are multiple linear regression analysis and moderation regression analysis using the SPSS version 25 program. The results of the study show that money ethics affects Tax Evasion. Information Technology has no effect on Tax Evasion. As for intrinsic religiosity and extrinsic religiosity as variable moderation does not succeed in moderating in this relationship both on money ethics and information technology taxation. Keywords : Money ethics, Information technology taxation, Intrinsic, Extrinsic Religiosity, Tax Evasion